Kepemimpinan Transformasional Kepala Sekolah di Lembaga Pendidikan Islam - sahri sahri; Achmad Fatoni; Binti Maunah (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2023)
Leadership increases individual and group trust, generates awareness and interest within groups and organizations and tries to move subordinates' attention to the achievements and growth of educational institutions. The interaction between the leader and subordinates in transformational leadership, characterized by the influence of the leader to change the behavior of his subordinates into someone who feels capable and highly motivated and strives to achieve high and quality work achievements. This research uses library research so that what is used in this research is a literature study. The results of this study show that transformative leadership is a leader who is able to influence or direct subordinates in an effective way to achieve organizational goals that have been set together. In transformative leadership, the leader sets an example for subordinates and motivates them by providing a clear and inspiring vision of the future. Leaders also support individual development and growth, provide constructive feedback, and facilitate open and collaborative communication. Transformative leaders also promote innovation and creativity, and enable team members to actively participate in the decision-making process. In this way, transformative leadership creates a positive and productive environment, leading to better outcomes and higher job satisfaction for everyone involved.